Mapping the environments, motivation and sport through bibliometric analysis from 2004 to 2024 - Anggorojati, Ayodya Satryo; Koestoer, Raldi Hendro; Sudarwati, Lilik (Jurnal Keolahragaan, 2025)
In order to create a better environment for sporst activities, abibliometric research exploring the relationship between environment, motivation, and sport globally. This study investigates the significant increase in scientific publications on the topic from 2004 to 2023, with a noted decline in 2024. This research using VOSviewer to anlalyse the tren and relationship refer to the scientific publication of the environment, motivation and sports topics. The International Journal of Environmental Research and Public Health emerged as a major contributor, accounting for 35 articles published. Significant patterns of author collaboration were uncovered, with an average of 2.67 authors per article, highlighting a concentration among a select group of top authors. Dominant research themes such as “Motivation,” “Sports,” “Health,” and “Education” were identified through the keyword co-occurrence network, indicating robust interrelationships. Analysis of co-author relationships between countries underscores the pivotal contributions of nations including the United States, United Kingdom, China, Germany, and France, underscoring the importance of cross-country collaboration in research advancement. This research offers insights into the evolving landscape of environmental and motivational factors in sport, providing a comprehensive overview of international trends, collaborations, and research foci. These findings serve to guide future research endeavors and inform decisions pertaining to global initiatives promoting healthy and motivated environment for sports activities, grounded in scientific evidence.